Motivation to Purchase Decisions Through TikTok Shop: Motivasi dalam Keputusan Pembelian Melalui Toko TikTok - Ari Fradita Dewi Susanti; Ainur Rochmaniah (Academia Open, 2024)
This research aims to describe and elucidate the influence of motivation and lifestyle on purchasing decisions through TikTok Shop. Employing a quantitative approach, the study utilized statistical techniques to examine the relationship between two independent variables (X) and the dependent variable (Y). The research focused on production employees in a selected area, with 90 respondents sampled through purposive sampling. Data collection involved the distribution of questionnaires through Google Forms, and the analysis was conducted using multiple linear regression in SPSS 18.0. The results reveal a significant simultaneous influence of motivation and lifestyle on purchasing decisions through TikTok Shop, supported by a partial impact indicated by the t-test. The correlation coefficient of 0.844 signifies a strong positive relationship between the independent and dependent variables. This study contributes to the understanding of consumer behavior in the context of social commerce platforms like TikTok Shop, offering valuable insights for marketers and researchers alike. Highlights : Quantitative Analysis: Utilizing statistical methods to examine the impact of motivation and lifestyle on purchasing decisions through TikTok Shop. Employee Focus: Targeting production employees as the study participants, providing insights into the consumer behavior of this specific demographic. Strong Positive Relationship: Revealing a robust correlation coefficient of 0.844, emphasizing a significant and positive association between motivation, lifestyle, and purchasing decisions on TikTok Shop. Keywords: TikTok Shop, Motivation, Lifestyle, Purchasing Decisions, Social Commerce